Palestinian women of Gaza and the West Bank - Sabbagh, Suha (Indiana University Press, 1998)
This collection introduces the reader to the women of Arab/Palestinian society, their social and political roles, and the challenges they face. In her introduction, Suha Sabbagh outlines the role of women in the struggles of Gaza and the West Bank. She demonstrates that neither the international media nor Arab commentators have accurately assessed the contributions of women's institutions or the support of traditional women for the Intifada. What impact will the politicization of these traditional women have on the predicated social transformations in the emerging Palestinian state? Will the women seek to alter their role in society, and what will be the response to their attempts? The essays in this multidisciplinary work, written from an "insider's" perspective, seek to answer these questions.